2014
DOI: 10.1186/1756-0500-7-222
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and school bag use: a cross-sectional study among Ugandan pupils

Abstract: BackgroundThough seen as a convenient method of carrying books and other scholastic materials including food items, schoolbags are believed to contribute to back and other musculoskeletal problems in school going children. This study set out to determine the prevalence of low back and other musculoskeletal pains and describe their relationship with schoolbag use in pupils.ResultsThis was a cross-sectional descriptive study involving 532 pupils from six primary schools with a mean age of 13.6 years. Analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
6
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(131 citation statements)
references
References 22 publications
9
99
6
17
Order By: Relevance
“…Students who spent eight or more hours per day in sedentary activities had approximately three times more likely to suffer from back pain than those spent five hours or less per day. This result was in agreement with [38] they assessed musculoskeletal pain and school bag use Effect on Back Pain Occurrence Among School Children among Ugandan pupils. They showed that there was a significant correlation between the time pupils spent sitting and the occurrence of back pain.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Students who spent eight or more hours per day in sedentary activities had approximately three times more likely to suffer from back pain than those spent five hours or less per day. This result was in agreement with [38] they assessed musculoskeletal pain and school bag use Effect on Back Pain Occurrence Among School Children among Ugandan pupils. They showed that there was a significant correlation between the time pupils spent sitting and the occurrence of back pain.…”
Section: Discussionsupporting
confidence: 81%
“…This findings was supported by the results of other studies [43,45,46] revealed that longer periods of time spent carrying a school bag each day influences cervical, shoulder and lumbar posture and could contribute to the musculoskeletal pain. Likewise, a study conducted by [38] revealed that the duration of time spent by the children carrying their school bags had a significant positive correlation with the occurrence of reported back pain. As regards perception of schoolbag weight in the present study, schoolchildren who reported that their school bags heavy were 2.4 times more likely to suffer from back pain than school children who were not having this feeling This result was in line with [35] that confirmed a significant association between reported weight of the backpack and pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoolbag weight and duration of carriage have been investigated within the same studies, but independent of each other [1,4,24,[26][27][28]. However fundamental biomechanical principles of load and energy consumption suggest that schoolbag weight, and the exposure to that weight, should be investigated in combination with each other in order to acquire a measure of the mechanical burden that results from carrying a schoolbag.…”
Section: Introductionmentioning
confidence: 99%
“…Although the duration of carriage has been reported [1,4,20,[23][24][25][26][27][28], the systematic assessment of the utility of cut-off values for duration of carriage in identifying schoolbag-related discomfort has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%